Study to evaluate the role of TNFα, IL1β, IL6 in diagnosis and severity assessment of neonatal sepsis among term, appropriate for gestational age newborns - Arijit Bhowmik; Moumita Samanta; Avijit Hazra; Avranil Goswami; Somosri Ray; Tapas Kumar Sabui (Perinatal Medicine Foundation, 2021)
Objective There is no established diagnostic test available to diagnose neonatal sepsis. Tumor necrosis factor a (TNFα), interleukin 1b (IL1β) and interleukin 6 (IL6) showed some promising results in some recent studies in this respect, but their roles in diagnosis and prognosis of neonatal sepsis are not yet conclusive. In this study, we have tried to identify diagnostic and prognostic ability of these biomarkers in neonatal sepsis. Methods In this cross-sectional study, blood sample for 3 cytokines were collected at diagnosis of neonatal sepsis fulfilling diagnostic criteria by purposive sampling and values were compared with normal healthy newborns. Each of the cytokines was evaluated separately to identify, whether they can detect neonatal sepsis with at least 70% sensitivity and specificity. At the same time, their prognostic values were also evaluated in terms of disease severity and mortality. Results Among twenty normal newborns, standard deviation values of TNFα, IL1β and IL6 were 39.7±21.5 pg/ml, 34.6±20.9 pg/ml and 44.4±33.0 pg/ml, respectively. In sepsis group (n=40), these values were 69.6±26.0 pg/ml, 57.7±29.0 pg/ml and 204.6±169.2 pg/ml, respectively. All these differences were statistically significant (p<0.05). IL6 was able to diagnose neonatal sepsis with 80% (95%CI 64.4 to 90.9) sensitivity and 85% (95% CI 62.1 to 96.8) specificity considering a cut off value of 61.8 pg/ml with area under the curve 0.899. This result was better than other two biomarkers. Conclusion IL6 may be considered as a good diagnostic tool for neonatal sepsis. None of the biomarkers were able to prognosticate neonatal sepsis.